2015
DOI: 10.1124/jpet.115.229054
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Nitric Oxide Mediates Caffeine Antagonism of Alcohol-Induced Cerebral Artery Constriction

Abstract: Despite preventive education, the combined consumption of alcohol and caffeine (particularly from "energy drinks") continues to rise. Physiologic perturbations by separate intake of ethanol and caffeine have been widely documented. However, the biologic actions of the alcohol-caffeine combination and their underlying subcellular mechanisms have been scarcely studied. Using intravital microscopy on a closed-cranial window and isolated, pressurized vessels, we investigated the in vivo and in vitro action of etha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 64 publications
3
19
0
Order By: Relevance
“…This approach has been widely used for studies with direct clinical implications (González et al, 1999;Aukes et al, 2007;Fike et al, 2012). With regards to alcohol research, several important findings first obtained in pressurized vessels were successfully validated in vivo (Bukiya et al, 2014, Chang et al, 2016. Thus, our current results are likely to provide mechanistic explanations to the earlier observation that dietary CLR protected cerebral arteries from alcohol-induced constriction in vivo via CLR buildup within VSM (Bukiya et al, 2014).…”
Section: Discussionsupporting
confidence: 57%
“…This approach has been widely used for studies with direct clinical implications (González et al, 1999;Aukes et al, 2007;Fike et al, 2012). With regards to alcohol research, several important findings first obtained in pressurized vessels were successfully validated in vivo (Bukiya et al, 2014, Chang et al, 2016. Thus, our current results are likely to provide mechanistic explanations to the earlier observation that dietary CLR protected cerebral arteries from alcohol-induced constriction in vivo via CLR buildup within VSM (Bukiya et al, 2014).…”
Section: Discussionsupporting
confidence: 57%
“…This approach replicates the in vivo response of cerebral vessels to alcohol, as was consistently demonstrated by our group [13,15]. Arteries were dissected out, pressurized at 60 mmHg and probed with 50 mM ethanol.…”
Section: Resultsmentioning
confidence: 80%
“…This study is important, because endothelial dysfunction is commonly present in hypertensive elderly patients. Interestingly, in T2DM (type 2 diabetes mellitus) elderly patients, Gilchrist et al 45 did not observed any change in both diastolic and systolic BP after 2 week of beetroot juice supplementation (with 7.5 moles of nitrate per day) neither improvements in endothelial function or insulin sensitivity Chang J et al 46 Further research is needed, because evaluated patients who were making drug use (to control co morbidities associated to T2DM), which might affect vascular function and them the response to inorganic nitrate. Gilchrist et al assessed neither plasma nitrite nor NO, this is necessary because NO response to inorganic nitrate supplementation varies widely between health and unhealthy elderly Lundberg JO et al 47 A recent meta-analysis Larsen FJ et al 48 evaluated data of beetroot juice supplementation effect on 24-hr ABPM (ambulatory blood pressure monitoring) in older subjects, it was concluded that nitrite concentrations, followed by inorganic nitrate ingestion, works as a potential factor influencing the association between inorganic nitrate and vascular responses.…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, caffeine with NO availability works as a protective combination during ethanol induced cerebral artery constriction. 46 Analyzing these two substances from the literature results we can assume that acute inorganic nitrate or inorganic nitrate rich meals consumption can decrease BP enough to modulate caffeine's impact on the elderly BP Siervo M et al 51 (Table 3) shows that inorganic nitrate vascular effects are contrary to those promoted by caffeine consumption. In young subjects, inorganic nitrate consumption has been show to improve mitochondrial efficiency 48 which is related to its cryogenic potential.…”
Section: Discussionmentioning
confidence: 99%